DEVELOPMENT OF METHOD OF DECODING BLOCK CODES BASED ON DIFFERENTIAL EVOLUTION PROCEDURE - Kozlovskyi, Valerii; Stompel, Mykola; Lysechko, V.; Komar, Oleksii; Drobyk, V. (Science-based technologies, 2023)
The approach of soft decoding of block codes based on determining the most reliable basis of the generator matrix and applying the differential evolution procedure is proposed. The choice of this search optimization procedure was made as a result of the analysis of the features and limitations of evolutionary optimization procedures. The scheme and the essence of the main stages of the developed method of soft decoding of block codes are presented. At the first stage, a hard decision is formed and the received word syndrome is calculated. After that, the received symbols are ranked by reliability and the generator matrix of the block code is transformed into the corresponding most reliable basis. Next, a differential evolution procedure is applied to search for the most probable transmitted information message and a binary codeword. Decoding is completed by inverse transformation of the found most probable binary codeword by rearranging the corresponding elements. It is shown that the key stage of decoding is the search for the transmitted codeword using the differential evolution procedure, and the formation of the most reliable basis of the generator matrix of block code makes it possible to increase the decoding efficiency. In order to be able to technically implement this decoding method, an appropriate algorithm has been developed and its main steps are given. The results of the work can be used for the implementation of new generation radio communication technologies to improve the reliability of the transmission of service messages. It is also recommended to use the obtained results when solving the problem of decoding other error-correcting code structures that are used in modern telecommunication technologies.